Congenital hypofibrinogenemia: a case report - Paramesh, Pandala; Thota, Usha Rani; Kotha, Rakesh (International Journal of Contemporary Pediatrics, 2021)
Fibrinogen disorders are rare bleeding disorders. Fibrinogen is also called factor I which is involved in last step of coagulation cascade. Congenital hypofibrinogenemia is usually caused by mutation of FIB (fibrinogen-binding protein) gene. These disorders should be suspected when Thrombin time is prolonged in well look child with history of bleeding manifestations. We are describing a female child who is having pallor with history of recurrent ecchymosis and minor post traumatic bleeding. Based on coagulation screening profile, we made the diagnosis of hypofibrinogenemia.